Skills of vocational education in the aspect of development accounting in the organs of social insurance - Muqadamkhon Zokirkhonovna Abdurahmonova (International Journal of Education and Learning, 2021)
In this article some directions of professional development in the sphere of accounting just in the organs of social insurance are considered. Also the trends of social insurance that is social pensions are defined. In the result of research based the main skills of vocational education and directions of development accounting aspect of social insurance organs. In the result of changes in some aspects of accounting, that is in methods of accrues, percentage of deductions, recording transactions in accounts and so on, appeared necessary in development vocational skills of accounting in the aspect of insurance system. Offered formulas influence to the process of development professional achievements in the sphere of social insurance. Classified the main deductions of salary in accordance to international standards and brought sample accounting entries of usually accounting operations. In total, by our opinion high quality courses of accounting for practical accountants influence to the process of accounting development. World practice has proven that the market economic system has certain significant shortcomings, which include unemployment, inflation, population differentiation by income level, etc. Along with this, in the conditions of the dominance of market relations, the population is at a certain risk of losing their job, a permanent source of income or the ability to work. Hence, the issues of social protection of the population from negative market phenomena become one of the important tasks of a civilized state. In addition, in the harsh market conditions, social support for those who are unable to work, who are retired, receive medical treatment, below the poverty line, as well as those who have not yet reached working age, who work in low-paid, but important socially important positions, in general, in need of external assistance becomes a priority function of the state.